Readiness Analysis for the Implementation of Electronic Medical Records in Private Medical and Dental Practices: Readiness for EMR Implementation in Private Practices - Rachmatulaili; Indasah; Nurwijayanti (CV. Paperhome Indonesia, 2025)
Background: The implementation of Electronic Medical Records (EMR) is part of the digital transformation of the healthcare system in Indonesia. However, the readiness of primary healthcare facilities, such as private medical and dental practices, varies. The purpose of this study is to analyze the readiness for Electronic Medical Records (EMR) implementation in terms of human resources, work culture, governance and leadership, and infrastructure in private medical and dental practices in Pasuruan City. Method : The research design used a qualitative approach with a case study approach. Informants were selected through observation and interviews with 20 general practitioners and doctors practicing independently at private medical practices and private dental practices located in the city of Pasuruan. This study used purposive sampling techniques. The research instrument used an interview guide. Data collection was conducted in June 2025. Results: The research findings revealed that most respondents understood the basic concepts of Electronic Medical Records (EMR) and had adequate equipment to support its use. Work culture exhibits adaptive characteristics, although there are still barriers in the form of limited training and manual work habits, particularly among senior medical staff. Decision-making regarding Electronic Medical Records (EMR) implementation tends to be top-down, with the practice owner playing a central role. Basic infrastructure such as hardware is available, but internet connectivity and application interoperability remain the primary challenges. Conclusion: In general, the readiness for Electronic Medical Records (EMR) implementation in private medical and dental practices in Pasuruan City is already at a positive early stage. However, full success requires strengthening human resource capacity through continuous training, improving the stability of digital infrastructure, and policy synergy between the government and professional organizations so that EMR implementation runs optimally and sustainably